PENANGANAN BULLYING MELALUI PENGUATAN KARAKTER PADA ANAK USIA SEKOLAH DASAR - Dea Rakhimafa Wulandari (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Bullying in Indonesia is not a new thing, but a case that is very familiar and even continues to increase every year. Cases of bullying occur in various aspects, including in the world of basic education. The age of school children 6-12 years is one of the factors that influence bullying. Behavior Bullying can certainly have a short-term and long-term impact on the victim. This study aims to analyze the description of bullying behavior in elementary age children and strategies for dealing with bullying carried out in elementary age children. This study used a qualitative descriptive research method. The results of the research are the following forms of bullying: (1) Physical bullying, including hitting, kicking, pushing, (2) Verbal bullying, including: mocking, calling friends by other names or the names of their parents, mocking, and giving bad words. (3) Mental bullying, including: exclusion of other students. The implementation of character strengthening is carried out through three strategies, namely: integrating character values ??in the teaching and learning process, through scouting activities, and through school culture. KeyWord: Bullying, Character Strengthening, Elementary Age Children